A Critical Review On the Management of Kukunaka with Special Reference to Neonatal Conjunctivitis: LifeScience-Ayurveda - Kapatkar, Dr.Shruti; Rathi, Dr. Renu; Thakre, Dr Trupti; Panda, Dr.Manisha (International Journal of Life Science and Pharma Research, 2023)
In Ksheerapa avastha, kukunaka is a specific inflammatory eye illness that most commonly affects infants under eight months.Kukunaka is mentioned as Vartmagata Kapha-Raktaj disease of eye. It is a Bala Netrarog linked to photophobia and ocular weakening.The most prevalent eye condition affecting infants is kukunaka, associated with neonatal conjunctivitis or Ophthalmia neonatorum.Local irritation, microorganisms, and the herpes simplex virus are the main causes of inflammation. It happens due to postpartumdifficulties or infections and maternal infections during labor and delivery. Because of an allergic reaction, the child keeps rubbing theirforehead, eyes, nose, and throat. This condition is characterized by watering and purulent discharge from both eyes and keratitis oruveitis may also be present. A neonate with neonatal conjunctivitis or ophthalmia neonatorum would have an inflamed conjunctiva.This review paper aims to review the management of Kukunaka from classical texts of Ayurveda. This review was conducted by learningAyurveda classical texts related to Kaumarbhrutya, Pediatrics texts on Neonatal diseases, published research journals on Pediatricdiseases, and electronic databases. This review's peculiarity is compiling all the data for kukunaka vyadhi from classic texts like its clinicalfeatures, causative factors, and various internal and external medications. Various formulations of kukunaka that are not studied yet areenlightened in this review, along with some shodhana karma that was indicated to nursing mothers and infants, are described in detail.The article concludes that this review is carried out for future research, which will be helpful for the management of kukunaka.